2012
DOI: 10.1104/pp.112.199646
|View full text |Cite
|
Sign up to set email alerts
|

RDR1 and SGS3, Components of RNA-Mediated Gene Silencing, Are Required for the Regulation of Cuticular Wax Biosynthesis in Developing Inflorescence Stems of Arabidopsis    

Abstract: The cuticle is a protective layer that coats the primary aerial surfaces of land plants and mediates plant interactions with the environment. It is synthesized by epidermal cells and is composed of a cutin polyester matrix that is embedded and covered with cuticular waxes. Recently, we have discovered a novel regulatory mechanism of cuticular wax biosynthesis that involves the ECERIFERUM7 (CER7) ribonuclease, a core subunit of the exosome. We hypothesized that at the onset of wax production, the CER7 ribonucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
86
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 50 publications
3
86
0
Order By: Relevance
“…Both of these proteins are involved in the synthesis of small RNAs. These results led to the hypothesis that uncharacterized small RNA species directly or indirectly mediate posttranscriptional silencing of CER3 to control cuticular wax deposition in developing Arabidopsis inflorescence stems (Lam et al, 2012).…”
Section: The Regulation Of Wax Biosynthesismentioning
confidence: 99%
“…Both of these proteins are involved in the synthesis of small RNAs. These results led to the hypothesis that uncharacterized small RNA species directly or indirectly mediate posttranscriptional silencing of CER3 to control cuticular wax deposition in developing Arabidopsis inflorescence stems (Lam et al, 2012).…”
Section: The Regulation Of Wax Biosynthesismentioning
confidence: 99%
“…CER7 encodes an exosomal exoribonuclease, and the cer7 mutant exhibits reductions in stem wax and transcription of CER3, a major wax biosynthetic enzyme (Hooker et al, 2007). Recently, two suppressors of cer7 that restore the CER3 transcript and stem wax levels were identified, and cloning of the respective genes identified RDR1 and SGS3, two conserved components of the RNA-mediated gene-silencing pathway (Lam et al, 2012). A model was proposed wherein CER7 is involved in the degradation of a small RNA species that negatively regulates the CER3 transcript.…”
Section: Beyond Transcription Factorsmentioning
confidence: 99%
“…A model was proposed wherein CER7 is involved in the degradation of a small RNA species that negatively regulates the CER3 transcript. Future work involving the identification of such a small RNA species and other components of this pathway will be especially intriguing, since no known plant small RNA species mapped to the CER7-dependent region of the CER3 promoter (Lam et al, 2012).…”
Section: Beyond Transcription Factorsmentioning
confidence: 99%
“…To gain additional insight into regulation of wax deposition by the CER7/RRP45B subunit, we carried out a screen for second-site suppressors of cer7-associated wax deficiency and isolated a series of wax restorer (war) mutants (Lam et al, 2012). Systematic identification of genes disrupted in these war lines revealed that the majority encode enzymes of the small interfering RNA (siRNA) biosynthetic pathway.…”
mentioning
confidence: 99%